2015
DOI: 10.1515/bmc-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Defense peptides: recent developments

Abstract: Defense peptides are small amphipathic molecules that exhibit antimicrobial, antitumor, antiviral, and immunomodulatory properties. This review summarizes current knowledge on the mechanisms of antimicrobial activity of cationic and anionic defense peptides, indicating peptide-based as well as microbial cell-based factors affecting this activity. The peptide-based factors include charge, hydrophibicity, and amphipathicity, whereas the pathogen-based factors are membrane lipid composition, presence of sterols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 130 publications
0
16
0
1
Order By: Relevance
“…Due to the unique properties of AMPs, they can and should be used for the benefit of humanity in the face of the antibiotic resistance catastrophe (Ventola, 2015). Existing efforts of scientific research are directed toward searching for more effective bactericides and studying of their mode of action (Cytryńska and Zdybicka-Barabas, 2015). Even though such investigations are necessary, there are some aspects of this problem that are poorly addressed by research.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique properties of AMPs, they can and should be used for the benefit of humanity in the face of the antibiotic resistance catastrophe (Ventola, 2015). Existing efforts of scientific research are directed toward searching for more effective bactericides and studying of their mode of action (Cytryńska and Zdybicka-Barabas, 2015). Even though such investigations are necessary, there are some aspects of this problem that are poorly addressed by research.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been proposed to explain the interactions of AMPs with microbial membranes, including the barrel-stave, carpet-like, aggregate, and toroidal pore model. Nevertheless, irrespective of the model, it is generally accepted that the initial step of the binding is mediated by electrostatic interactions between the cationic peptide and negatively charged membrane components followed by hydrophobic interactions between amphipathic domains in the peptide molecule and lipid components of the membrane (Nguyen et al 2011;Scocchi et al 2011;Cytryńska and Zdybicka-Barabas 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These investigations have also shown that there are a number of major drivers in the membrane interactions of AMPs of which the most important are charge, hydrophobicity and amphiphilicity [9,18,19]. The vast majority of AMPs are cationic to help facilitate the targeting of microbes through direct electrostatic interaction with anionic components of their membranes [19,20].…”
Section: Introductionmentioning
confidence: 99%